Retroviral coinfection (Jaagsiekte and Maedi-Visna viruses) in sheep with pulmonary tumors in Transylvania (Romania): retrospective study on 82 cases - Hodor, Dragoș; Toma, Corina; Negoescu, Andrada; Olech, Monika; Gordon, Dumitru; Cătoi, Cornel; Taulescu, Marian (Frontiers in Veterinary Science, 2024)
Ovine pulmonary adenocarcinoma (OPA) is an important viral-induced neoplasia in sheep caused by exogenous Jaagsiekte sheep retrovirus (exJSRV). Coinfection of exJSRV and Maedi-Visna virus (MVV) is reported in OPA cases, but its worldwide distribution and significance on lung pathology is not yet completely understood. This study aimed to investigate the MVV coinfection rate in 82 exJSRV-related OPA cases, and their pathological effects on lung parenchyma in slaughtered sheep in Transylvania (Romania). On gross examination, classical form of OPA was identified in 92.7%; no changes consisting with MVV interstitial pneumonia were identified in the included cases. The most common histological type of OPA was acinar (58.5%) and the myxoid growths were found in 18 cases. The exJSRV and MMV coinfection rate in examined sheep was 47.6% (39/82). The assessment of perineoplastic areas from coinfected animals, revealed interstitial lymphoplasmacytic infiltrates in all cases, lymphoid hyperplasia in 60.6% cases (20/33) and fibromuscular hyperplasia in 63.7% (21/33). This is the first report providing new data on distribution of OPA coexisting with MVV infection in slaughtered sheep in Romania. We consider that the OPA and MVV coinfection may play an important role on the severity of ovine chronic pulmonary diseases and further studies are needed to confirm this hypothesis.